Temperature, salinity and density of the surface waters of the Atlantic ocean. - Bohnecke, Gunther (Oxonian Press, 1991)
Scientific results of the German Atlantic Expedition of the Research Vessel Meteor, 1925-1927; vol. 5 with atlas